2012
DOI: 10.1539/joh.11-0150-oa
|View full text |Cite
|
Sign up to set email alerts
|

Work Ability Index (WAI) and Its Association with Psychosocial Factors in One of the Petrochemical Industries in Iran

Abstract: as job insecurity, skill discretion, job strain and social support play an important role in maintaining work ability. A positive combination of "psychosocial characteristics" of the job with "individual resources" can promote work ability in such occupations. Work ability is a multifaceted and multidetermined concept not only associated with health but also with competence, values, the working environment and social relations 1) . The level of work ability in the working population can predict both future per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
50
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 25 publications
15
50
2
6
Order By: Relevance
“…In addition, the results showed that people with physically demanding jobs, compared with those in mentally demanding jobs, underestimated their current work ability (the first dimension of WAI questionnaire). This finding was consistent with the findings reported by Finnish and Iranian researchers (6,14,23). With increasing age, the work ability of workers in physically demanding jobs reduces more than the workers in mentally demanding jobs (7).…”
Section: (N = 15)supporting
confidence: 94%
See 3 more Smart Citations
“…In addition, the results showed that people with physically demanding jobs, compared with those in mentally demanding jobs, underestimated their current work ability (the first dimension of WAI questionnaire). This finding was consistent with the findings reported by Finnish and Iranian researchers (6,14,23). With increasing age, the work ability of workers in physically demanding jobs reduces more than the workers in mentally demanding jobs (7).…”
Section: (N = 15)supporting
confidence: 94%
“…The differences observed between the results of this study and those of previous ones may be due to differences in several factors such as work environment, life style, nature of the job and mean age of the workers. Ergonomic corrections in the workstations and work environments was one of the most positive factors in the studied workplace which had a significant impact on maintaining the work ability of the personnel and thus their WAI was placed in a good range (6,7). In the current study, the WAI had little relationship with age; although some of the participants were younger, they had lower work ability than the older ones (aged over 45 years).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…A condição de vulnerabilidade 23 Considerando o pouco tempo de trabalho, este ICT é preocupante, embora não se possa afirmar que a perda da capacidade para o trabalho tenha relação com somente este último emprego das agentes de limpeza. No entanto, cabe refletir sobre a capacidade prejudicada para o trabalho apresentada por 27, 27% das participantes, pois isto aponta para a necessidade de rever as condições de trabalho e propor melhorias a partir de atividades de promoção de saúde, conforme proposto por Tuomi et al 22 e Silva et al 15 .…”
Section: Aspectos Relacionados à Capacidade De Trabalhounclassified